2020
DOI: 10.22319/rmcp.v11i4.5049
|View full text |Cite
|
Sign up to set email alerts
|

Serotipos y aislamientos de Escherichia coli productora del subtipo Stx2 de la toxina Shiga provenientes de canales y heces de ganado bovino

Abstract: Shiga toxin E. coli (STEC) is an important pathogen responsible for foodborne illness, this have been related with epidemic outbreaks in the past, mainly because of consumption of bovine meat. The objective of this study was identify the serotypes and Stx2 subtypes and associate them with their possible epidemiology. There were analyzed a total of 65 isolates from the collection of the Centro de Investigación y Estudios Avanzados en Salud Animal, Facultad de Medicina Veterinaria y Zootecnia of the Universidad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Possession of the stx genes by animal E.coli does not necessarily indicate that they cause disease. It has been suggested that ruminants in particular do not have vascular globotriaosylceramide receptors where Shiga toxin binds and are always asymptomatic [ 52 ]. However, the ruminants can easily shed Shiga toxin producing E. coli in their feces and are considered reservoirs for Shiga toxin producing E.coli for humans.…”
Section: Discussionmentioning
confidence: 99%
“…Possession of the stx genes by animal E.coli does not necessarily indicate that they cause disease. It has been suggested that ruminants in particular do not have vascular globotriaosylceramide receptors where Shiga toxin binds and are always asymptomatic [ 52 ]. However, the ruminants can easily shed Shiga toxin producing E. coli in their feces and are considered reservoirs for Shiga toxin producing E.coli for humans.…”
Section: Discussionmentioning
confidence: 99%
“…We set the following four treatment groups: control (vehicle: only alpha-MEM), LPS (Sigma, USA, 500 ng/mL), Stx (Toxin Technology, USA, 20 ng/mL), and LPS + Stx. We exposed iPSC-MSCs and HMEC-1 to Stx for 24 h. We used the type 2 variant of Stx (Stx2) as it is the most relevant in terms of epidemiology (13). In addition, as LPS is present in all gram-negative bacterial infections and is the main modulator of the inflammatory response, we use the combination of LPS + Stx for every experiment.…”
Section: Methodsmentioning
confidence: 99%